ANALISIS KESALAHAN BERBAHASA PRANCIS PEMANDU WISATA DI TANA TORAJA - Parura, Kidung Biantong; Junus, Fierenziana Getruida; Armin, Mardi Adi (JURNAL ILMU BUDAYA, 2020)
This article is the result of a study on "French Language Guide in Tana Toraja". This study aims to analyze the mistakes made by tour guides in Tana Toraja in French. The subjects in this study were 3 French-speaking tour guides, and the object in this study was a mistake in French. This study uses descriptive qualitative and quantitative analysis methods with a theory approach to analyzing language errors in the Tarigan model that divides language errors into misformation, omission, addition, and misorder which will then be searched for factors causing language errors by tour guides in Tana Toraja. After conducting research, the results of the analysis show that all tour guides make mistakes in French, and the most dominant tour guide makes mistakes is the tour guide 1. The error is caused by performance factors such as experience and communication goals and competency factors, namely education.